Réflexion sur l’indécidable flaubertien : à partir de la traduction de Bouvard et Pécuchet en japonais - Norioki Sugaya (Flaubert: Revue Critique et Génétique)
Having recently published the Japanese translation of Bouvard and Pécuchet, we will reflect on some characteristic features of the Flaubertian text that this experience has allowed us to deepen again. First, we will ask ourselves to what extent Flaubert's style, in particular the famous free indirect style, can be transferred into another language, whose grammatical organization and syntactic structure differ significantly from those of the French language. In a second time, we will deal with the problem of editing in general and try to measure the meaning of the semantic ambiguities of which we find many examples in the novel. This will result in relativizing a little the received modernist idea on Flaubert’s undecidability.